2018
DOI: 10.1021/acs.est.7b00377
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chemodiversity of Dissolved Organic Matter in Paddy Soils

Abstract: Organic matter (OM), and dissolved organic matter (DOM), have a major influence upon biogeochemical processes; most significantly, the carbon cycle. To date, very few studies have examined the spatial heterogeneity of DOM in paddy soils. Thus, very little is known about the DOM molecular profiles and the key environmental factors that underpin DOM molecular chemodiversity in paddy soils. Here, Fourier-Transform Ion Cyclotron Resonance Mass Spectrometry was applied to unambiguously resolve 11 361 molecular form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 58 publications
6
122
0
Order By: Relevance
“…While variations in the type and abundance of paddy soil DOM molecules have typically been chalked-up to temperature, moisture, pH, and mineralogy [ 15 , 27 29 ], here, we demonstrated that the microbiome describes DOM variance to a greater extent than any other edaphic or geographic factor investigated. This result emphasizes the overriding potential impact that biotic function factors can have on constructing the DOM heterogeneity when compared to other abiotic functions in paddy soil.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…While variations in the type and abundance of paddy soil DOM molecules have typically been chalked-up to temperature, moisture, pH, and mineralogy [ 15 , 27 29 ], here, we demonstrated that the microbiome describes DOM variance to a greater extent than any other edaphic or geographic factor investigated. This result emphasizes the overriding potential impact that biotic function factors can have on constructing the DOM heterogeneity when compared to other abiotic functions in paddy soil.…”
Section: Discussionmentioning
confidence: 52%
“…Factors like parential metrial, redox state, fertilization level, pesticide application, mineralogy, rice cultivar, and growth stage may also influence the geography of the microbial community and DOM [ 29 , 48 53 ]. In submerged paddy soil, rice aerenchyma enables the transport of atmospheric O 2 to the roots [ 54 ], influencing soil redox states [ 55 ]; moreover, rice straw and stubble are assumed to provide substrates for microbial activity in the early growth stage, while exudates become more important during late tillering and ripening [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FT-ICR MS analysis. Bulk DOM extractions were characterized by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) on a Bruker Apex-Ultra mass spectrometer equipped with a 9.4-T actively shielded superconducting magnet interfaced with a negative-ion-mode electrospray ionization system (31). Diluted Suwannee River natural organic matter solution (50 mg liter 21 ) (obtained from IHSS [the International Humic Substances Society]) was used as a control and injected every 18th sample to ensure instrument stability.…”
Section: Methodsmentioning
confidence: 99%
“…Two multivariate statistical methods, hierarchical cluster analysis (HCA) and principal component analysis (PCA), were used to evaluate the extent of similarities between the 113 samples (XLSTAT_2013 Version 19.03). With complex data sets, data compilation approaches are used to prepare data for multivariate analysis (Sleighter et al ; Li et al ). Three approaches based on the occurrence/absence of compounds in individual samples were used to generate sample‐specific chemical profiles that then served as inputs for the multivariate analyses.…”
Section: Methodsmentioning
confidence: 99%